A study of annular plate buckling problem with tension loaded at inner edge - Syed Abu Bakar, Syed Noh; Abdalla, Mostafa M.; Faris, Waleed Fekry ("Eftimie Murgu" University of Resita, 2010)
The buckling problem of annular plate with only one edge (either inner or outer edge) constrained is formulated and presented in this paper. The boundary condition is simply supported inner edge - free outer edge. The results are compared between the FEM results obtained using ABAQUS and results reported in literature. The results shows good agreement for critical buckling load, mode shapes and stress distributions.